2019
DOI: 10.18235/0001561
|View full text |Cite
|
Sign up to set email alerts
|

Public Financial Management, Health Financing and Under-Five Mortality: A Comparative Empirical Analysis

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license. Following a peer review process, and with previous written consent by the Inter-American Development Bank (IDB), a revised ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Piatti and Smets’s (2019) study showed that the higher the quality of budget management and PFM, the better the health system would perform and prevent the health systems from becoming more expensive to progress toward the SDGs ( 31 ). According to the results of this study, one of the major consequences of these budgeting and PFM challenges is increased spending, and consequently, the cost of services and care provided in the country's health system.…”
Section: Discussionmentioning
confidence: 99%
“…Piatti and Smets’s (2019) study showed that the higher the quality of budget management and PFM, the better the health system would perform and prevent the health systems from becoming more expensive to progress toward the SDGs ( 31 ). According to the results of this study, one of the major consequences of these budgeting and PFM challenges is increased spending, and consequently, the cost of services and care provided in the country's health system.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also make the link between use of country systems and improved health outcomes. For example, Piatti-Fünfkirchen and Smets (2019) found that a one-unit increase in PFM quality reduces the U5 mortality rate with about 14 deaths per 1,000 live births. For countries that channel at least 75 percent of public health expenditures through the government system, this rate increases to 17 deaths per 1,000 child births.…”
mentioning
confidence: 99%